Same strategy for pitfalls of radiotherapy in different anatomical districts. Issue 3 (April 2016) - Gobbo, Margherita; Ottaviani, Giulia; Rupel, Katia; Ciriello, Francesca; Beorchia, Aulo; Di Lenarda, Roberto; Zacchigna, Serena; Biasotto, Matteo
Abstract Oral mucositis (OM) and radiodermatitis (RD) are serious side effects of radiotherapy (RT), often leading to its suspension, need for analgesics, and enteral/parenteral nutrition. Laser therapy is becoming a recommended treatment option. This prospective study aimed at demonstrating the beneficial effect of class IV laser therapy (HPLT) on RT-induced OM, an off-label use of HPLT to treat RD in breast cancer patients. Fifty-three cancer patients, during/after RT and/or chemotherapy (CT), affected by OM, were treated with HPLT during four consecutive days (970 ± 15 nm, 5 W (50 %), 35–6000 Hz, 240 s). Assessment of OM (Grading Objective Scale, WHO-SCALE), pain (visual analogue scale, VAS), functional ability, subjective parameters, and site/severity of OM were recorded over time. Similarly, 27 breast cancer patients affected by RD were treated by HPLT and monitored over time for grade, discomfort, itching, and bleeding. Progressive improvement of WHO-SCALE from day 7 on, and of VAS from day 2 on (p  < 0.000) was registered. All patients' functional capacity improved on day 4 (p  < 0.05). All subjective parameters improved on day 14 (p  < 0.001) except for voice, which improved on day 21 (p  < 0.000). Ulcerations' dimension and erythema's severity significantly decreased in all sites examined (p  < 0.05). Similarly, HPLT proved to be beneficial in managing RD for all the parameters considered (p  < 0.002). Regardless of OM grade/site and of kind/site of tumor, HPLT proved to be effective in healing OM as well as RD. In both cases, effective treatment can improve life quality through a safe, easy, innovative approach. Therefore, HPLT may become an integral part of everyday practice in the management of RT adverse effects.